Inventarisasi produk yang mengandung rhodamin B pada jajanan makanan dan minuman di indonesia secara virtual literasi - Hasnia Nia (Jurnal Medika Hutama, 2021)
Rhodamine B is a synthetic dye that is commonly used as a textile dye, but should not be used in food products because the effects of consuming Rhodamine B can irritate the respiratory tract, skin, eyes, digestive tract, poisoning and liver disorders, as well as in the long term cancer and tumors. . Snacks are foods or drinks that are commonly found on the roadside which are sold in various shapes, colors, flavors, and sizes so as to attract people's interest and attention to buy them. Several studies have shown that in Indonesia there are still many people who do not understand the dangers of consuming rhodamine B. The making of scientific papers uses literature or literature study methods from several existing journals using secondary data collection techniques. The results obtained prove that in Indonesia there are still many people who use rhodamin B, as evidenced by several examinations by BPOM and journals. Of the 25 journals, there are 17 regions that still use rhodamine B while only 8 regions have not used Rhodamine. Keywords: Rhodamine B; snacks; literature study.